Nitride composite coating saw blade and preparation method thereof
By doping titanium carbide into the titanium nitride coating to form a TiN-TiC composite coating, the problem of easy wear of the existing titanium nitride coating is solved, the wear resistance and hardness of the saw blade are improved, and the service life is extended.
Patent Information
- Application Number
- CN202411819401.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing titanium nitride coating is prone to wear, resulting in a shorter life of the saw blade.
Titanium carbide doping deposition method is used to form a point in the titanium nitride to form a TiN-TiC composite coating to improve wear resistance and hardness.
It effectively improves the wear resistance and hardness of the nitride composite coating, extends the service life of the saw blade, and reduces the friction coefficient.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy cutting tools, and in particular relates to a nitride composite coating saw blade and a preparation method thereof. Background Art
[0002] With the continuous advancement of advanced manufacturing technology, high-speed and efficient cutting processing has become a trend in the development of advanced manufacturing. As an essential tool for cutting, saw blades also need to develop in the direction of high-speed and efficient cutting. Therefore, saw blades should have the characteristics of high hardness and heat resistance, and be able to maintain high hardness and wear resistance under high temperature and high pressure environments. The current saw blade structure is relatively simple, causing the saw blade coating to wear too quickly and the service life to be greatly reduced. Summary of the invention
[0003] In view of the problems in the prior art, the present invention provides a nitride composite coated saw blade, which solves the problem that the existing titanium nitride coating is easy to wear. Points are formed in the titanium nitride by titanium carbide doping deposition, thereby effectively improving the wear resistance and hardness of the nitride composite coating.
[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:
[0005] A nitride composite coating saw blade comprises a substrate and a nitride composite coating. The nitride composite coating adopts a TiN-TiC composite coating. Furthermore, titanium carbide is doped in the carbon nitride coating.
[0006] The method for preparing the nitride coated saw blade comprises the following steps:
[0007] Step 1, placing a circular saw blade in an ethanol aqueous solution and ultrasonicating it for 20-30 minutes, taking it out and placing it in a sodium hydroxide solution and stirring it for 20-30 minutes, filtering and cleaning it, and then drying it to obtain a circular saw blade with a clean surface, wherein the volume fraction of ethanol in the ethanol aqueous solution is 40-50%, the temperature of the ultrasonication is 50-60°C, the ultrasonic frequency is 60-80kHz, the pH of the sodium hydroxide solution is 9-10, the stirring speed is 500-1000r / min, the filtering and cleaning is carried out with distilled water, and the distilled water is used for cleaning until the cleaning solution is neutral, and the drying temperature is 120-140°C; this step uses the ethanol aqueous solution and the sodium hydroxide solution to clean the surface of the circular saw blade, which can not only completely remove surface impurities, but also use sodium hydroxide to emulsify and separate surface oil stains, thereby achieving a surface cleaning effect;
[0008] Step 2: spray dilute hydrochloric acid onto the surface of the circular saw blade, and let it stand at a constant temperature for 20-30 minutes, rinse and dry to obtain a circular saw blade with a rough surface. The pH of the hydrochloric acid is 5-7, and the spray volume of the spray is 0.5-1.2 mL / cm 2The constant temperature static temperature is 40-50°C, the rinsing adopts distilled water, and the drying temperature is 120-130°C; in this step, dilute hydrochloric acid is used for surface spraying to form a hydrochloric acid liquid film. During the constant temperature static, the dilute hydrochloric acid is uniformly distributed under the action of the liquid film, and forms in-situ corrosion on the circular saw blade, achieving stable and uniform surface corrosion treatment, and obtaining a circular saw blade with a rough surface after drying;
[0009] Step 3: Add titanium tetrachloride to ethanol and stir evenly to obtain a low concentration solution, then spray it onto the surface of the circular saw blade, and let it stand at a constant temperature for 20-30 minutes to obtain a circular saw blade with a surface film. The concentration of titanium tetrachloride in ethanol is 50-80 g / L, the stirring speed is 200-400 r / min, and the spraying amount is 3-4 mL / cm 2 , the temperature of the constant temperature static is 80-100°C; in this step, titanium tetrachloride is uniformly dispersed in ethanol, and a liquid film is deposited on the surface of the circular saw blade by spraying, and the circular saw blade can be completely covered by the fluidity of the liquid film itself, and the ethanol is removed in situ by constant temperature static, thereby forming a titanium tetrachloride film, which covers the rough surface of the circular saw blade;
[0010] Step 4, placing the circular saw blade containing the surface film in a reactor for constant temperature reaction for 2-3 hours, and then performing a secondary constant temperature reaction for 6-7 hours after purging with argon to obtain a pre-plated circular saw blade, wherein the atmosphere of the reactor is a mixed atmosphere of argon and ammonia, and the volume ratio of argon to ammonia is 3-5:1, the temperature of the constant temperature reaction is 30-50°C, and the temperature of the secondary constant temperature reaction is 450-500°C; this step uses a gas-liquid reaction system to fix ammonia on titanium tetrachloride, thereby achieving a nitrogen fixation effect;
[0011] Step 5, placing the coated circular saw blade into a deposition reaction chamber for vapor deposition to obtain a coated tool, wherein the atmosphere in the deposition reactor is titanium tetrachloride, methane and argon, wherein the molar ratio of titanium tetrachloride to methane is 1:1.02-1.06, the vapor deposition pressure temperature is 900-1000°C, and the pressure is 6-8kPa; this step utilizes methane and titanium tetrachloride to form a titanium carbide deposition, and at the same time, the pre-plated layer gaps on the pre-plated circular saw blade are infiltrated by titanium carbide, thereby forming a nitride composite layer of titanium carbide doped with titanium nitride.
[0012] It can be seen from the above description that the present invention has the following advantages:
[0013] 1. The present invention solves the problem of easy wear of the existing titanium nitride coating, and forms points in the titanium nitride by means of titanium carbide doping deposition, thereby effectively improving the wear resistance and hardness of the nitride composite coating.
[0014] 2. The present invention solves the problem of poor adhesion of titanium carbide itself, uses titanium nitride to form a bridge, and cooperates with the co-sintering stability of titanium carbide and titanium nitride to form a high-hardness composite coating system. DETAILED DESCRIPTION
[0015] A specific embodiment of the present invention is described in detail in conjunction with the embodiments, but no limitation is imposed on the claims of the present invention.
[0016] Example 1
[0017] A method for preparing a nitride coated saw blade comprises the following steps:
[0018] Step 1, placing a circular saw blade in an ethanol aqueous solution and ultrasonicating it for 20 minutes, taking it out and placing it in a sodium hydroxide solution and stirring it for 20 minutes, filtering and cleaning it, and then drying it to obtain a circular saw blade with a clean surface, wherein the volume fraction of ethanol in the ethanol aqueous solution is 40%, the temperature of the ultrasonication is 50° C., the ultrasonic frequency is 60 kHz, the pH of the sodium hydroxide solution is 9, the stirring speed is 500 r / min, the filtering and cleaning is carried out with distilled water, and the distilled water is used for cleaning until the cleaning solution is neutral, and the drying temperature is 120° C.;
[0019] Step 2: spray dilute hydrochloric acid onto the surface of the circular saw blade, and let it stand at a constant temperature for 20 minutes, rinse and dry to obtain a circular saw blade with a rough surface. The pH of the hydrochloric acid is 5, and the spray volume is 0.5 mL / cm 2 The constant temperature is 40°C, the rinsing is done with distilled water, and the drying is done at 120°C.
[0020] Step 3: Add titanium tetrachloride to ethanol and stir evenly to obtain a low concentration solution, then spray it onto the surface of the circular saw blade, and let it stand at a constant temperature for 20 minutes to obtain a circular saw blade with a surface film. The concentration of titanium tetrachloride in ethanol is 50 g / L, the stirring speed is 200 r / min, and the spraying amount is 3 mL / cm 2 , the constant temperature is 80℃;
[0021] Step 4, placing the circular saw blade containing the surface film in a reactor for isothermal reaction for 2 hours, and then performing a secondary isothermal reaction for 6 hours after argon purging to obtain a pre-plated circular saw blade, wherein the atmosphere of the reactor is a mixed atmosphere of argon and ammonia, and the volume ratio of argon to ammonia is 3:1, the temperature of the isothermal reaction is 30°C, and the temperature of the secondary isothermal reaction is 450°C;
[0022] Step 5, placing the coated circular saw blade into a deposition reaction chamber for vapor deposition to obtain a coated tool, the atmosphere in the deposition reactor is titanium tetrachloride, methane and argon, wherein the molar ratio of titanium tetrachloride to methane is 1:1.02, the vapor deposition pressure temperature is 900°C, and the pressure is 6 kPa.
[0023] The thickness of the nitride composite coating in the saw blade prepared in this embodiment is 3.3 μm, the hardness is 2600 HV, and the friction coefficient is 0.52.
[0024] Example 2
[0025] A method for preparing a nitride coated saw blade comprises the following steps:
[0026] Step 1, placing a circular saw blade in an ethanol aqueous solution and ultrasonicating it for 30 minutes, taking it out and placing it in a sodium hydroxide solution and stirring it for 30 minutes, filtering and cleaning it, and then drying it to obtain a circular saw blade with a clean surface, wherein the volume fraction of ethanol in the ethanol aqueous solution is 50%, the temperature of the ultrasonication is 60° C., the ultrasonic frequency is 80 kHz, the pH of the sodium hydroxide solution is 10, the stirring speed is 1000 r / min, the filtering and cleaning is carried out with distilled water, and the distilled water is used for cleaning until the cleaning solution is neutral, and the drying temperature is 140° C.;
[0027] Step 2: spray dilute hydrochloric acid onto the surface of the circular saw blade, and let it stand at a constant temperature for 30 minutes, rinse and dry to obtain a circular saw blade with a rough surface. The pH of the hydrochloric acid is 7, and the spray volume is 1.2 mL / cm 2 The constant temperature is 50°C, the rinsing is done with distilled water, and the drying is done at 130°C.
[0028] Step 3: Add titanium tetrachloride to ethanol and stir evenly to obtain a low concentration solution, then spray it onto the surface of the circular saw blade, and let it stand at a constant temperature for 30 minutes to obtain a circular saw blade with a surface film. The concentration of titanium tetrachloride in ethanol is 80 g / L, the stirring speed is 400 r / min, and the spraying amount is 4 mL / cm 2 , the constant temperature is 100℃;
[0029] Step 4, placing the circular saw blade containing the surface film in a reactor for isothermal reaction for 3 hours, and then performing a secondary isothermal reaction for 7 hours after argon purging to obtain a pre-plated circular saw blade, wherein the atmosphere of the reactor is a mixed atmosphere of argon and ammonia, and the volume ratio of argon to ammonia is 5:1, the temperature of the isothermal reaction is 50° C., and the temperature of the secondary isothermal reaction is 500° C.;
[0030] Step 5, placing the coated circular saw blade into a deposition reaction chamber for vapor deposition to obtain a coated tool, the atmosphere in the deposition reactor is titanium tetrachloride, methane and argon, wherein the molar ratio of titanium tetrachloride to methane is 1:1.06, the vapor deposition pressure temperature is 1000°C, and the pressure is 8kPa.
[0031] The thickness of the nitride composite coating in the saw blade prepared in this embodiment is 3.5 μm, the hardness is 2700 HV, and the friction coefficient is 0.51.
[0032] Example 3
[0033] A method for preparing a nitride coated saw blade comprises the following steps:
[0034] Step 1, placing a circular saw blade in an ethanol aqueous solution and ultrasonicating it for 25 minutes, taking it out and placing it in a sodium hydroxide solution and stirring it for 25 minutes, filtering and cleaning it, and then drying it to obtain a circular saw blade with a clean surface, wherein the volume fraction of ethanol in the ethanol aqueous solution is 45%, the temperature of the ultrasonication is 55° C., the ultrasonic frequency is 70 kHz, the pH of the sodium hydroxide solution is 10, the stirring speed is 800 r / min, the filtering and cleaning is carried out with distilled water, and the distilled water is used for cleaning until the cleaning solution is neutral, and the drying temperature is 130° C.;
[0035] Step 2: spray dilute hydrochloric acid onto the surface of the circular saw blade, and let it stand at a constant temperature for 25 minutes, rinse and dry to obtain a circular saw blade with a rough surface. The pH of the hydrochloric acid is 6, and the spray volume is 0.9 mL / cm 2 The constant temperature is 45°C, the rinsing is done with distilled water, and the drying is done at 125°C.
[0036] Step 3: Add titanium tetrachloride to ethanol and stir evenly to obtain a low concentration solution, then spray it onto the surface of the circular saw blade and let it stand at a constant temperature for 25 minutes to obtain a circular saw blade with a surface film. The concentration of titanium tetrachloride in ethanol is 70 g / L, the stirring speed is 300 r / min, and the spraying amount is 4 mL / cm 2 , the constant temperature is 90℃;
[0037] Step 4, placing the circular saw blade containing the surface film in a reactor for isothermal reaction for 3 hours, and then performing a secondary isothermal reaction for 7 hours after argon purging to obtain a pre-plated circular saw blade, wherein the atmosphere of the reactor is a mixed atmosphere of argon and ammonia, and the volume ratio of argon to ammonia is 4:1, the temperature of the isothermal reaction is 40° C., and the temperature of the secondary isothermal reaction is 480° C.;
[0038] Step 5, placing the coated circular saw blade into a deposition reaction chamber for vapor deposition to obtain a coated tool, the atmosphere in the deposition reactor is titanium tetrachloride, methane and argon, wherein the molar ratio of titanium tetrachloride to methane is 1:1.04, the vapor deposition pressure temperature is 950°C, and the pressure is 7 kPa.
[0039] The thickness of the nitride composite coating in the saw blade prepared in this embodiment is 3.4 μm, the hardness is 2650 HV, and the friction coefficient is 0.52.
[0040] Comparative Example
[0041] The comparative example uses a commercially available titanium nitride coated saw blade. The thickness of the nitride composite coating in the saw blade prepared in this example is 3.4 μm, the surface hardness is 2300 HV, and the friction coefficient is 0.55.
[0042] From the data comparison of the above-mentioned embodiments 1-3 and the comparative example, it can be seen that the technical solution doped titanium carbide on the surface of the titanium nitride coating, effectively improved the surface hardness of the saw blade, and the friction coefficient was lower than that of the titanium nitride coating, which effectively extended the service life of the coating. At the same time, when the saw blades of embodiments 1-3 and the saw blades of the comparative example were used for saw blade experiments, when processing martensitic stainless steel solid bars, under the same linear speed and single tooth feed rate, the sawing life of the nitride composite coating saw blade provided by the present invention was significantly better than that of the titanium nitride coating saw blade of the comparative example.
[0043] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A nitride composite coated saw blade, characterized in that: The invention comprises a circular saw blade substrate and a nitride composite coating, wherein the nitride composite coating adopts a TiN-TiC composite coating.
2. The nitride composite coated saw blade according to claim 1, characterized in that: The titanium carbide is doped in the carbon nitride coating.
3. The nitride composite coated saw blade according to claim 1, characterized in that: The method for preparing the nitride coated saw blade comprises the following steps: Step 1, placing a circular saw blade in an ethanol aqueous solution and ultrasonicating it for 20-30 minutes, taking it out and placing it in a sodium hydroxide solution and stirring it for 20-30 minutes, filtering and cleaning it, and then drying it to obtain a circular saw blade with a clean surface; Step 2, spraying dilute hydrochloric acid onto the surface liquid film of the circular saw blade, and standing at a constant temperature for 20-30 minutes, rinsing and drying to obtain a circular saw blade with a rough surface; Step 3, adding titanium tetrachloride to ethanol and stirring evenly to obtain a low-concentration solution, and then spraying it onto the surface of the circular saw blade, and standing at a constant temperature for 20-30 minutes to obtain a circular saw blade containing a surface film; Step 4, placing the circular saw blade containing the surface film in a reactor for constant temperature reaction for 2-3 hours, and then purging with argon gas for a second constant temperature reaction for 6-7 hours to obtain a pre-plated circular saw blade; Step 5, placing the coated circular saw blade into a deposition reaction chamber for vapor deposition to obtain a coated tool.
4. The nitride composite coated saw blade according to claim 3, characterized in that: The volume fraction of ethanol in the ethanol aqueous solution in step 1 is 40-50%, the temperature of the ultrasound is 50-60°C, the frequency of the ultrasound is 60-80kHz, the pH of the sodium hydroxide solution is 9-10, the stirring speed is 500-1000r / min, the filtration and cleaning is carried out with distilled water, and the distilled water is used for cleaning until the cleaning solution is neutral, and the drying temperature is 120-140°C.
5. The nitride composite coated saw blade according to claim 3, characterized in that: The pH of the hydrochloric acid in step 2 is 5-7, and the spray volume of the spray is 0.5-1.2 mL / cm 2 The constant temperature static temperature is 40-50°C, the rinsing adopts distilled water, and the drying temperature is 120-130°C.
6. The nitride composite coated saw blade according to claim 3, characterized in that: The concentration of titanium tetrachloride in ethanol in step 3 is 50-80 g / L, the stirring speed is 200-400 r / min, and the spray volume is 3-4 mL / cm 2 , the constant temperature is 80-100℃.
7. The nitride composite coated saw blade according to claim 3, characterized in that: The atmosphere of the reactor in step 4 is a mixed atmosphere of argon and ammonia, and the volume ratio of argon to ammonia is 3-5:
1. The temperature of the isothermal reaction is 30-50°C, and the temperature of the secondary isothermal reaction is 450-500°C.
8. The nitride composite coated saw blade according to claim 3, characterized in that: The atmosphere in the deposition reactor in step 5 is titanium tetrachloride, methane and argon, wherein the molar ratio of titanium tetrachloride to methane is 1:1.02-1.06, the pressure temperature of the vapor deposition is 900-1000°C, and the pressure is 6-8kPa.
Citation Information
Patent Citations
Method for preparing abrasion resistant coating layer of cutter
CN101591780A
Double-blade milling cutter
CN111482644A
Wear-resisting saw bit
CN202344616U
Saw blade with coating
CN204053110U
Method and device for the preparation of protective layer by plasma deposition
CN86106364A